Influence of group size on the degree of individual learning - Talačka , V. (Psichologija, 1980)
The article deals with the influence of group size on the degree of individual learning in cooperation. The experiments carried out show that individual learning is influenced by numbers, the best results having been achieved by the students who worked in twos
Keywords: group; groups size; individual learning